The characteristics of two soil toposequences on basement complex in the Federal Capital Territory of Nigeria - FAGBAMI , A. A.; UDO, E. J. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Morphological, physical, chemical and mineralogical characteristics of Gwagwa and Kau soil toposequences, were studied. These toposequences are representative of the Basement Complex soils of the Federal Capital Territory of Nigeria. The soils are light-textured and moderately acidic. They have low organic matter and low effective CEC but high base saturation. Kaolinite is the most abundant clay mineral. The upland soils which have reddish hues are classified as Alfisols but the soils in the valley bottom and interfluvial depressions with brownish to yellowish hues are classified as Entisols or Inceptisols. The Gwagwa profiles have gravel layers or stonelines probably formed by pedimentation proceses. The Kau toposequence is characterised by rock outcrops associated with colluvial footslope plains